Design and Evaluation of a Healthcare Management Terminology Mobile Learning Application - Vani, B. Madhura; T. Gayathri,; S. Sujitha,; Prof. V. Sujatha,; Lakshmi, Dr.S. Maha (The journal of contemporary issues in business and government, 2019)
The EZ-HCM App, a mobile learning tool for healthcare management terminology, is being developed in this project. We created a questionnaire using a five-point Likert scale based on the technology acceptance model (TAM) to explore students' impressions of the utility, ease of use, attitude toward usage, and intention to use the EZ- HCM App. Between July 2016 and June 2017, research participants were university students from Taiwan's fourth biggest Department of Health Care Management. To understand students' design needs for a healthcare management terminology translation dictionary and explanation, we use the persona technique. Following the development of the EZ-HCM App, 113 students from the department were asked to take part in pre- and post-testing surveys, as well as the EZ-HCM App Acceptance Questionnaire. There were seventy valid surveys returned. The findings revealed that the EZ-HCM App is widely accepted for its utility (mean=4.40, SD=0.46), ease of use (mean=4.49, SD=0.48), attitude toward usage (mean=4.42, SD=0.49), and intention to use (mean=4.15, SD=0.58). Participants' perceptions of the EZ-HCM App's usefulness and simplicity of use do not alter based on their frequency of smartphone use. The EZ-HCM App's acceptability is similar to that of other m-learning systems, with favourable attitudes toward usage (β =0.77, p.0001; β =0.47, p=.0002) and intention to use (β =0.87, p.0001; β =0.98, p.0001) among participating students.